2021
DOI: 10.3390/agriculture11080772
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on Grain Quality and Pesticide Residues in Maize Stored in Hermetic and Polypropylene Storage Bags

Abstract: The conventional method of grain storage involving the use of polypropylene bags in conjunction with pesticides and hermetic bags are paramount in developing countries. However, there is limited information on grain quality and pesticide residue concentration of maize stored in such bags. This work determined grain quality and pesticide residue concentrations of maize stored in polypropylene and hermetic storage bags. Maize samples stored for a period of one year in polypropylene and hermetic bags were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Hermetic storage had no detrimental effects on the percentage of germination and applying percussion or delaying the germination assay did not significantly improve it. These results corroborate the findings of García-Lara et al [ 33 ] and Odjo et al [ 14 ] in the central highlands of Mexico and experiments elsewhere [ 34 , 47 , 48 , 49 ]. Hermetic technologies preserve the percentage of seed germination by limiting oxygen availability and maintaining low-equilibrium relative humidity for stored seed, which in turn slows oxidative reactions associated with decreased seed viability [ 50 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hermetic storage had no detrimental effects on the percentage of germination and applying percussion or delaying the germination assay did not significantly improve it. These results corroborate the findings of García-Lara et al [ 33 ] and Odjo et al [ 14 ] in the central highlands of Mexico and experiments elsewhere [ 34 , 47 , 48 , 49 ]. Hermetic technologies preserve the percentage of seed germination by limiting oxygen availability and maintaining low-equilibrium relative humidity for stored seed, which in turn slows oxidative reactions associated with decreased seed viability [ 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results are similar to those from other experiments in the State of Mexico published by García-Lara et al [ 33 ], who reported an increase in grain moisture content stored using polypropylene sacks. The same results have also been reported for experiments elsewhere [ 34 , 35 ]. These changes are associated with environmental humidity and the failure of polypropylene woven bags to protect grain from external conditions, potentially increasing moisture content or drying stored grain, depending on the environment [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…Examples of this can be methods and means on the basis of which the determination of the process of grain respiration is made: on the accumulation of carbon dioxide; by reducing the oxygen content (Latyshenok et al, 2021), by the loss of dry mass of grain (Baributsa et al, 2021); by changing the pressure in a container filled with grain (manometric methods) (Aduchayev, 2015); by determining the amount of heat that was released during the study (Nyarko et al, 2021).…”
Section: Review Of Previous Researchmentioning
confidence: 99%
“…Educating smallholder farmers on the benefits of hermetic storage bags, and promoting adoption of this innovative chemical-free protection technology, should continue to be a priority among supply chain actors to ensure food-safe maize from producers to consumers [1]-Consortium; (2) Apply dynamic controlled atmosphere technologies to reduce incidence of physiological disorders and maintain quality of apples. 'Granny Smith' apples stored under repeated low oxygen stress (RLOS) in combination with ultra-low oxygen (ULO) or controlled atmosphere (CA) conditions, and under dynamic controlled atmosphere (DCA) conditions in combination with chlorophyll fluorescence (CF) treatment had significantly (p < 0.05) higher flesh firmness and total soluble solids.…”
Section: Recent Innovations In Post-harvest Preservation and Protection Of Agriculturalmentioning
confidence: 99%